2020
DOI: 10.1371/journal.pone.0229182
|View full text |Cite|
|
Sign up to set email alerts
|

The views, perspectives, and experiences of academic researchers with data sharing and reuse: A meta-synthesis

Abstract: BackgroundFunding agencies and research journals are increasingly demanding that researchers share their data in public repositories. Despite these requirements, researchers still withhold data, refuse to share, and deposit data that lacks annotation. We conducted a meta-synthesis to examine the views, perspectives, and experiences of academic researchers on data sharing and reuse of research data. MethodsWe searched the published and unpublished literature for studies on data sharing by researchers in academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 62 publications
0
55
0
2
Order By: Relevance
“…Aspects of researchers' experiences and attitudes about sharing research data are, relative to other aspects of open science, well-studied. A meta-synthesis of 45 qualitative studies of researchers' practices and perceptions about data sharing found that researchers lack time, resources, and skills to effectively share their data in public repositories (Perrier et al 2020). In previous research, a lack of suitable infrastructure for data sharing is commonly cited as a barrier to the availability of research data along with a lack of incentives (Science et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of researchers' experiences and attitudes about sharing research data are, relative to other aspects of open science, well-studied. A meta-synthesis of 45 qualitative studies of researchers' practices and perceptions about data sharing found that researchers lack time, resources, and skills to effectively share their data in public repositories (Perrier et al 2020). In previous research, a lack of suitable infrastructure for data sharing is commonly cited as a barrier to the availability of research data along with a lack of incentives (Science et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, some scientific disciplines are significantly ahead in terms of data sharing, for example in genomics [ 66 ], as confirmed in the present study for molecular epidemiology in animal species. In other disciplines, barriers to making research datasets available have been explored [ 57 , 61 , 67 , 68 ] and some of the factors which can positively impact data sharing have been identified [ 69 – 71 ]. Top-down pressure, in the form of strong encouragement or policies of mandatory sharing, from funding bodies and journal publishers appears to be highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Systematic reviewers should share review data, analytic code and other materials routinely; (ii) Potential facilitators or barriers apply to the sharing of systematic review material, which we will draw from previous studies examining facilitators and barriers to adopting open science practices [41][42][43][44][45][46][47].…”
Section: Survey Contentmentioning
confidence: 99%